PKM KONSEP PENANAMAN POHON UNTUK EKOWISATA DI DESA CIMARGA KECAMATAN CIMARGA KABUPATEN LEBAK - Juhandi Juhandi; Friska Lia Imelda; Tb. Yumba Kamafih; Tiafani Zumaniar (Yayasan Education and Social Center, 2021)
Cimarga Village is one of the Lokasi Villages in CimargaSubdistrict. The problems faced by Cimarga Village are among others, the reduction of water catchment areas due to the transfer of land functions into settlements. This happens because the tourism sector is starting to develop and encourage high physical development such as homestays, housing, and supporting infrastructure. Agricultural activities also tend to change the hue of nature. Many trees that trerletak in the field must be cut down so as not to block the sunlight. As a result rainwater also cannot be absorbed into the ground but flows to the surface. In addition, cimarga village is also vulnerable to landslides. This is because the location of the village is in the highlands and the number of critical land scattered. In addition, these critical lands are not covered with plant vegetation so that they are prone to landslides in the rainy season. Even many critical land is located very close to the settlement of the population and is actually used as agricultural land. This condition is certainly dangerous for the safety of local people. Moreover, cimarga village becomes one of the tourist villages, so the aspect of disaster mitigation should always take precedence. There are many vacant lots that have not yet been utilized. In fact, if used, in addition to increasing the coverage of green areas is also beneficial for the welfare of the community through the results of the tree. Therefore, the greening movement in cimarga village needs to be one of the urgent programs to be carried out immediately. So that later it will indirectly support the existing role so far as a vocational village and tourist village. The plants planted are a type of annual perennial, considering that fruit commodities are not so good when planted in the highlands besides that perennials have a strong rooting system and the ability to deliver oxygen. Some commodities that can be grown include fir, red shoots, Dutch teak and acacia. The selection of perennials because it is expected to produce wood in the next few years and supply oxygen so that it can strengthen kopeng village as an ecotourism area